2004
DOI: 10.1590/s1413-78522004000100004
|View full text |Cite
|
Sign up to set email alerts
|

Modelo de suspensão pela cauda e seu efeito em algumas propriedades mecânicas do osso do rato

Abstract: silience). 53 adult female rats were used and distributed in four groups according to the length of time in suspension (control, 7, 14 and 21 days). The model of suspension was efficient with good animals adaptation and it caused a significant weakness of bones mainly in the 21-day period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
3
0
2
Order By: Relevance
“…Furthermore, we observed that jump training prevented loss of body mass. These findings are in agreement with other studies ( 18 , 23 , 29 , 30 ).…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, we observed that jump training prevented loss of body mass. These findings are in agreement with other studies ( 18 , 23 , 29 , 30 ).…”
Section: Discussionsupporting
confidence: 94%
“…However, this procedure may lead to hemostatic and morphofunctional disorders in bone tissue, with a consequent decrease of their mechanical properties. (2,15) In this study, the used immobilization generated a reduction in the number of osteocytes and a reduction in the diameter of the medullary canal (µm) in all immobilized groups when compared to CG. Nonetheless, the cortical thickness was significantly reduced only in the ICG and IMG when compared to the CG.…”
Section: Discussionmentioning
confidence: 82%
“…(15) This result seems to be associated with the decrease in bone metabolism, which causes a decrease in the cells number of the maintenance of this tissue. (15)(16)(17)(18) According to studies by Yeh et al, (16) the immobilization protocol allows the reabsorption and depression of the bone formation, results in decreased bone mass relative to its volume and simultaneously changes the material and geometric properties of the bone. It is estimated that about 30% of the bone loss induced by immobilization experiment in rats is caused by increase of bone resorption and about 70% by decreased bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…The animals included on groups S, S-R and S-T were suspended by tail for 28 days, and all procedures for hanging the animals by the tail were based on the study by Silva and Volpon (12) , who used a suspension model developed from a description by Kasper et al (13) . For preparing animals' tails for suspension, the rats were anesthetized by intramuscular injection of a combination of 30mg/kg and 3mg/kg ketamine and xylazine, respectively.…”
Section: Animal Suspensionmentioning
confidence: 99%